Early Land Plants Today: Index of Liverworts & Hornworts 2011–2012 - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
A widely accessible list of known plant species is a fundamental requirement for plant conservation and has vast applications. An index of published names of liverworts and hornworts between 2011 and 2012 is provided as part of a continued effort in working toward producing a world checklist of this group. The list includes 25 higher taxa, 154 species, 31 infraspecific taxa, and 17 autonyms for 2011 and 2012, 12 of them are fossils. A few taxa not covered by the earlier indices for 2000–2010 are also included. 75 species and 15 infraspecific taxa are new to science.